A new species of Minuartia (Caryophyllaceae) restricted to the high Andes of South America - Nicola, Marcela Viviana (2013)
A new apetalous species of Minuartia from the high Andes of northwestern Argentina, M. altoandina, is here described and illustrated. At first sight, M. altoandina is morphologically very similar to the European M. sedoides because of the absence of petals and ciliate leaf margin with narrow hyaline teeth; however, from a biogeographical point of view, it will probably be related to the North American M. rossii complex through the morphology of M. austromontana.